(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Local governments play a very important role in promoting the country's sustainable development, as they greatly influence the country's economic, social and territorial development. In turn, it is important for residents of municipalities to see that changes are taking place as a result of their participation. One of the ways of involving residents is through a participatory budget. Successful cooperation experience could promote greater trust of residents in their local government, better understanding of the activities of the local government. Democratization and decentralization of public administration are currently relevant in Latvia. In 2025, a participatory budget, which is required by law, must be introduced in all local governments in Latvia. In Latvia, less than half of all 43 local governments have tested a participatory budget by 2025. The association "Public Policy Centre PROVIDUS" has been a support and advisor to local governments, encouraging local governments to take steps towards cooperation with residents and to improve this process with each passing year. The aim of this study is to investigate the inclusion of residents in the management of municipal processes through participatory budgeting. Recognizing the importance of residents' involvement in the participatory budgeting process, the study will analyse the awareness, understanding and opinion of residents of all Latvian municipalities about the participatory budgeting process. The theoretical part of the study uses a monographic or descriptive method, but a survey of randomly selected respondents covering all local governments in the country is used to obtain primary data. The results of the study will allow Latvian municipalities to understand the significance and importance of participatory budgeting.